Molecular and immunological comparison of membrane-bound, H2-oxidizing hydrogenases of Bradyrhizobium japonicum, Alcaligenes eutrophus, Alcaligenes latus, and Azotobacter vinelandii. - Arp, D J (1985)
The membrane-bound hydrogenases of Bradyrhizobium japonicum, Alcaligenes eutrophus, Alcaligenes latus, and Azotobacter vinelandii were purified extensively and compared. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of each hydrogenase revealed two prominent protein bands, one near 60 kilodaltons and the other near 30 kilodaltons. The migration distances during nondenaturing polyacrylamide gel electrophoresis were similar for all except A. vinelandii hydrogenase, which migrated further than the other three. The amino acid composition of each hydrogenase was determined, revealing substantial similarity among these enzymes. This was confirmed by calculation of S delta Q values, which ranged from 8.0 to 26.7 S delta Q units. S delta Q is defined as sigma j(Xi,j-Xk,j)2, where i and k identify the proteins compared and Xj is the content (residues per 100) of a given amino acid of type j. The hydrogenases of this study were also compared with an enzyme-linked immunosorbent assay. Antibody raised against B. japonicum hydrogenase cross-reacted with all four hydrogenases, but to various degrees and in the order B. japonicum greater than A. latus greater than A. eutrophus greater than A. vinelandii. Antibody raised against A. eutrophus hydrogenase also cross-reacted with all four hydrogenases, following the pattern of cross-reaction A. eutrophus greater than A. latus = B. japonicum greater than A. vinelandii. Antibody raised against B. japonicum hydrogenase inhibited B. japonicum hydrogenase activity to a greater extent than the A. eutrophus and A. latus activities; no inhibition of A. vinelandii hydrogenase activity was detected. The results of these experiments indicated remarkable homology of the hydrogenases from these four microorganisms.